The notion of public official in Polish Criminal Law - Pieszczek, Martyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2013)
The article explains the meaning of the notion of public official in Polish criminal law. The paper consists of three parts. The first part is an introduction to the issue, which is the research problem verified by the article. The author defines the context of using the notion „public official” in the special part of the Polish Criminal Code and analyses the factors which have an impact on legal definition of this notion. The second part is dedicated to the study of legal definition of public official specified in article 115 § 13 of the Polish Criminal Code. The author focuses on the interpretation of those elements which have the most doubtful meaning. The third part is a conclusion of considerations presented in the article. The author attempts to evaluate the method used to define the notion „public official” in Polish Criminal Law and indicates the causes of difficulties in practical application of art. 115 § 13 of the Polish Criminal Code. Key words: public official, public function, abuse of power, legal definition of public official, criminal liability of public official, criminal protection of public official, offences against the functioning of the state and local government institutions.
Keywords: historia prawa; prawo publiczne; prawo prywatne; teoria prawa